Effects of different particle size of spinel and Y2O3 additive of the periclase-spinel refractory on the sintering densification and corrosion resistance to copper smelting slag. Issue 13 (1st July 2022) - Quan, Zhenghuang; Wang, Zhoufu; Liu, Hao; Ma, Yan; Wang, Xitang; Dong, Yunjie; Deng, Chengji; Fu, Gaofeng
Abstract: In order to analyze the sintering densification and copper smelting slag corrosion resistance of periclase-spinel refractories, the periclase-spinel refractories were prepared with fused magnesia, magnesia-rich spinel, industrial alumina, and yttrium oxide as the main raw materials. The different particle sizes of spinel in material and with or without Y2 O3 additive were studied. The study demonstrated that: (1) The different particle sizes of spinel in periclase-spinel refractories can result in different effects. Adding particle spinel to the refractory can improve the strength and corrosion resistance of the periclase-spinel refractories. The addition of spinel and magnesia powders in the matrix resulted in cracks due to the great difference of coefficient of thermal expansion between magnesia and spinel. The reduction in bulk density and strength of the material decreased slag penetration resistance because of its poor sintering properties. While adding the alumina in the matrix can further fill the crack and prevent slag penetration by the volume expansion of in-situ reaction to form spinel. (2) The periclase-spinel refractories can be reacted with Cu slag to form a Mg2 FeO4 insulating layer as the iron ion becomes oxidized. Adding Y2 O3 in periclase-spinel refractories can result in grain boundary phase reconstruction, which can promote sintering densification, improve the slag physical infiltration resistance, and improve the chemical corrosion resistance of materials.